PERANCANGAN SISTEM INFORMASI DOKUMENTASI KEGIATAN DAN PENGELOLAAN IURAN PADA LINGKUNGAN RUKUN TETANGGA (RT) BERBASIS WEB : Perancangan Sistem Informasi Dokumentasi Kegiatan dan Pengelolaan Iuran Pada Lingkungan Rukun Tetangga (RT) Berbasis Web - Monika Yuliana Yustrinita (2020)
RT (Rukun Tetangga) is a means of bridging the relationship between citizens and local governments, the most important role is to serve the citizens in carrying out an activity and convey information about what is happening in the RT environment. But, based on field observations, there are problems in the process of documenting activities and dues reports on the ongoing system, such problems as repeated recording processes, the length, the use of paper media that can cause the search process and reporting process is quite a time consuming and also the use of paper media that has a risk-prone to damage or loss. To solve the problem, RT requires a system that can help ease the work of the members of the RT administrators and also help residents get information. In this study, researchers used Waterfall as its development method and Unified Modeling Language (UML), while for the creation of applications, researchers used PHP and MySQL as their database. This research resulted in an application documenting the activities and management of web-based dues for the RT environment that is capable of providing guest report management, cover letters, submission of activity information, and a dues-managed report that can expedite the process of service and also the delivery of information to residents.